MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA KONSEP IMAN KEPADA RASUL-RASUL ALLAH MELALUI PEMBELAJARAN KOOPERATIF MODEL NHT DI KELAS VB SDN 2 RAMPA KOTABARU (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2022)
This class action research aims to determine the increase in student learning activities the concept of faith in the apostles of Allah through cooperative learning of the NHT model in the VB class of SDN 2 Rampa Kotabaru, To find out the improvement of student learning outcomes through cooperative learning of the NHT model konsep faith in the apostles of Allah.  This research using the NHT model of cooperative learning which is carried out as many as 2 cycles. Each cycle consists of planning, implementing actions, observation and reflection. The technique used in data collection in this study were observations and tests.  Bbased on the results of data analysis; The increase in student activity in learning from 61.79% to 98.81%. Learning outcomes also increased from 67.86% to 89.27%, with an average learning outcome become 71.43. The conclusion of this study is that the use of cooperative learning of the NHT model can increase the activities and learning outcomes of students with the concept of having faith in Allah's Apostles, so that NHT model cooperative learning can be used as an alternative in the implementation of learning Islamic Religious Education and Ethics. Keywords: NHT Model, Activity and Outcome learned.